Profile Scanning of the Farmers of Karimnagar District of Telangana State, India - N. Venkateshwar Rao; L.Mahesh; J.Vijay; D.Sreenivasa Reddy; A.Prashanthi; G.Venugopal; G.Prabhakar (Archives of Current Research International, 2024)
This research highlights the profile of farmers in Karimnagar district, Telangana. The study uses an ex-post facto and exploratory research design to analyse the socio-economic characteristics of farmers who adopted and those who did not adopt the technologies introduced by Krishi Vigyan Kendra (KVK), Jammikunta. The study includes 300 farmers who adopted KVK technologies and 150 who did not. Results show that the majority (43.00%) of the KVK-adopted farmers were of middle age, with 26.34% having primary-level education and 42.33% having high exposure to mass media. In contrast, the non-adopted farmers exhibited lower socio-economic and technological engagement. The research provides insights into the factors influencing the adoption of agricultural technologies.